The Profit-Sharing System Between Landowners and Cultivators of Tobacco : Islamic Economic Law Perspective - Susanti, Dyah Ochtorina (Kertha Patrika, 2021)
This research aims to find profit-sharing system between landowners and cultivators of tobacco based on Islamic Economic Law, so that it can be used by landowners and cultivators to cooperate in cultivating  tobacco fields. The method in this research using the normative legal research with the statute approach, and conceptual approach. The  results of the study in the form of 3 (three) forms of profit-sharing systems between landowners and tobacco cultivators according to Islamic economic law, which can be used, namely muzara'ah, mukhabarah, and musaqah. In the final part of this research, the researcher also provides advice to landowners and cultivators to put the cooperation agreement into written form, to prevent conflicts and disputes in the future. Further suggestions are addressed to the Government. The government needs to socialize the production sharing system in agriculture according to Islamic economic law.